A proposal for the dance reconstruction of Tony Fabella's Ang Kasal - Fabella, Anna Camille B.
This study aims to explore the feasibility of reconstructing undocumented dances in Philippines, in hopes of bringing back forgotten masterpieces, such as Ang Kasal, using anthropological and archaeological devices and methods, in order to thoroughly analyze the limited data on the production. Ang Kasal will be used as the sole case study for this paper. Through these findings, it is the author's hope that the beginning of a dance reconstruction practice in the country might take place. It also presents the many sources for further research on the piece to form a foundation for possible reconstruction as a full theatrical production once again, from the firsthand experiences of the cast to the traditional dances and practices Fabella might have been influenced by. In doing so, this study also formally documents the limited information on Ang Kasal and preserves these in an academic setting.